SISTEM INFORMASI LAPORAN PENILAIAN BARANG MILIK NEGARA BERBASIS WEB ( STUDI KASUS: KPKNL KISARAN ) - Jeperson Hutahaean; Zulfi Azhar (RJOCS (Riau Journal of Computer Science), 2018)
Assessment is Assessment Report which contains a description of the object of assessment, assessment goals, field survey date, date of assessment, data analysis, assessment approach, and the value conclusion. The design of the website is to discuss the design of the State Property Data Rate in KPKNL - Range. Website designed using PHP and MySQL with reports as penyimpannya MySQL Database. The main purpose of this system design is designing a new system to overcome the weaknesses that exist in the current system, to increaseefficiency in the processing time and data access. Where the design Websiste Data Information System Assessment Report of State Property in KPKNL - The range is done by using the design and development of the system towards better